Significance of Nuclear p-Akt in Endometrial Carcinogenesis: Rapid Translocation of p-Akt Into the Nucleus by Estrogen, Possibly Resulting in Inhibition of Apoptosis. Issue 2 (1st January 2011) - Abe, Naoya; Watanabe, Jun; Tsunoda, Shinpei; Kuramoto, Hiroyuki; Okayasu, Isao
Abstract : Introduction: Endometrial endometrioid adenocarcinoma (endometrial cancer) develops through endometrial hyperplasia caused by estrogenic hyperstimulation. Estrogen is known to activate growth factor signaling pathways, resulting in cellular proliferation, but precisely how has not been clarified. The aim of this study was to investigate the significance of estrogen and downstream factors such as the MAPK (MEK, ERK) and Akt pathways in endometrial carcinogenesis. Methods: The expression of p-MEK, p-ERK, and p-Akt was analyzed immunohistochemically in normal, hyperplastic, and neoplastic endometria. The estrogenic effect on p-Akt was examined using an endometrial cancer cell line (Ishikawa cells). The estrogenic effect on the apoptosis of Ishikawa cells was assessed by the TUNEL method. Results: Phospho-MEK (p-MEK) and p-ERK expression levels were similar among histological types but correlated with each other. The nuclear p-Akt labeling index (LI) was higher in cancer than in normal endometrium and hyperplasia. The nuclear p-Akt LI of well-differentiated cancer (G1) was higher than that of moderately (G2) or poorly (G3) differentiated cancers. The nuclear expression of p-Akt was correlated with that of estrogen receptor α (ER-α). The nuclear p-Akt level was significantly correlated with prognosis in cases of G1. In Ishikawa cells transfected with ERα, p-Akt was translocated into the nucleus from the cytoplasm in 1 to 3 hours after estrogenic stimulation. Further, apoptosis induced by H2 O2 was inhibited by estrogen in the ER-α-positive cells. Conclusions: The translocation of p-Akt into the nucleus by estrogen may be related to the suppression of apoptosis by estrogen and consequently to endometrial carcinogenesis and prognosis in G1 endometrial cancer.